THE ASSOCIATION OF INSULIN RESISTANCE AND LIPID PROFILE RATIO IN METABOLIC SYNDROME - Rini Rahmayani; Adi Koesoema Aman; Santi Safril (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
The cause of metabolic syndrome is still not known for sure, but it is suspected that the pathophysiology of metabolic syndrome is associated with insulin resistance and central obesity. Researchers have attempted to evaluate insulin resistance using various serum lipid concentration ratio. This study was to observe the association between insulin resistance and lipid profile ratio using HOMA-IR in metabolic syndrome patients. This study was a cross-sectional that was conducted in Inpatient and Outpatient Adam Malik Hospital during March 2016 - April 2016. Subjects were patients with metabolic syndrome criteria according to the International Diabetic Federation 2005. All samples were examined for their waist circumference, weight, height, blood pressure, insulin, serum glucose, total cholesterol, HDL cholesterol, LDL cholesterol, Triglycerides. Among sixty-six patients in the study 40 (60.6%) were male and 26 (39.4%) female. In this study, there was a significant correlation between HOMA-IR with CT/HDL ratio (r: 0.244 p <0.05); and there was no correlated HOMA-IR, and TG/HDL ratio (r: 0.086 p > 0.05) and there was no correlation between HOMA-IR and LDL/HDL (r: 0.336 p > 0.05). There was a significant relationship between insulin resistance and ratio CT/HDL